Islamic mysticism and transliminality: Factor and network analysis in Iranian Muslim students - Zhuo Job Chen; Nima Ghorbani (Social Sciences and Humanities Open)
The layered hierarchy model of mysticism recognizes the unitary core present in monistic mysticism, while also acknowledging the diverse range of experiences influenced by religious principles and individual dispositions. Within Islamic mysticism, these elements are encapsulated, emphasizing a tripartite synergy involving inner knowledge of the divine unity, adherence to religious codes of conduct, and the pathway that connects exoteric actions to esoteric truths. This study delves into these complexities by examining transliminality in a sample of 1033 Iranian Muslim students. Factor analysis and exploratory graph analysis revealed three factors underlying the revised transliminality scale, each with distinct meanings. The mysticism factor demonstrated support for Islamic religiosity and spirituality, aligning with integrative self-regulation as a Muslim ideal. Conversely, the hyperesthesia factor was incongruent with these ideals, exhibiting affective maladaptation. The absorption factor was uniquely linked to creative disposition while also indicating aspects of personality and affective maladaptation. These results underscore the intricacies within both Islamic mysticism and the transliminality construct, encouraging further exploration into the intricate interplay between mysticism, transliminality, and the rich tapestry of Islamic spirituality.